Effect of Chicken Bile Application on Scar Healing Process - limanda, Claudia Felicia; Intizam, Marwa Humaira; Jusuf, Pierre Joshua; Tanujaya, Monica Aprilia; Rusyati, Luh Made Mas (Explorer Front, 2023)
Type of scars varies from mild fine line scars to abnormal scars which treatment will differ according to its type, site, symptoms, and severity. Scars have a great impact of human life, namely physically, aesthetically, psychologically, and socially that make choosing the right treatment very important. Treatment for scars can be done conventionally in health care facilities and traditionally. Chinese traditional medicine has been known to have a major role in scar treatment. One of the examples is the use of chicken bile.